Basin-scale Paleoecology: Using Semi-quantitative Analysis of the Ichnofabric within Kutai Basin (Indonesia) - Ery Arifullah; Yahdi Zaim; Aswan; Djuhaeni (Journal of Mathematical and Fundamental Sciences, 2021)
Ichnofossils are still not used in paleoecological studies, even though they are a valuable proxy for paleoecology. This study focused on a semi-quantitative approach to a number of ichnofabric variables, i.e. ichnofossil association, bioturbation index (BI), ichnodiversity (ID), number of behaviors (NB), penetration depth (PD), and burrow diameter (DM). It was proved that the scores of those variables were low to medium because of the paleoecological fluvial-marine transition depositional processes in the Serravallian-Tortonian interval in Kutai Basin, Indonesia. This paper contributes an ichnofabric model that is visualized as histograms. One histogram shows the most common ichnofossil associations found in ichnofabric units, i.e., Ophiomorpha, Skolithos, Paleophycus, Planolites, Thalassinoides, and Chondrites. The other histograms describe the ichnofabric variables scores for BI, ID, NB, PD, and DM. The variables represent low to medium scores, a characteristic of a brackish paleoecology at basin-scale, a unique indicator for the fluvial-marine transition depositional system.